A meta-analysis of union rate after proximal scaphoid fractures: terminology matters. Issue 5 (3rd October 2022) - Chong, Han Hong; Kulkarni, Kunal; Shah, Rohi; Hau, Melinda Y. T.; Athanatos, Lambros; Singh, Harvinder Pal
Abstract: Heterogeneity in the anatomical definition of 'proximal' affects the comparison of outcomes of these scaphoid fractures. This study aims to review published outcomes of all variants to determine both, differences in terminology, and union rate based upon definition. A literature search was conducted to identify articles that reported descriptions and union rate of all acute (<8 weeks of injury) proximal scaphoid fractures in adult patients (>16 years old). Proximal fractures were grouped as reported ('third', 'pole', 'fifth' or 'undefined'). The data were pooled using a fixed-effects method, and a meta-analysis was conducted to compare relative risk (RR) of non-union against non-proximal fractures. Qualitative analysis of 12 articles included three main definitions: 'proximal' (1 article), 'proximal third' (3 articles), and 'proximal pole' (8 articles). Only 6 articles adopted a specific anatomical or ratio description. In a pooled meta-analysis of union rates (15 articles), 'proximal third' and 'proximal pole' fractures demonstrated a relative risk (RR) of non-union of 2.3 and 3.4 in comparison to non-proximal fractures, respectively. Operative management yielded lower non-union rates than non-operative for all fracture types (6% vs. 18%). In conclusion, non-union risk varies depending on definition, with non-standardised classifications adding heterogeneity to reported outcomes. We recommend an approach utilizing fixed anatomical landmarks on plain radiographs (referencing scaphoid length and scapho-capitate joint) to standardise reporting of proximal fracture union in future studies. Abbreviations : CI: confidence intervals; CT: computer tomography; Df: degrees of freedom; DL: dersimonian and laird estimator; MRI: magnetic resonance imaging; NICE: national institute for health and care excellence; OTA: orthopaedic trauma association; PA: posterior-anterior; PRISMA: preferred reporting items for systematic reviews and meta analyses; RCT: randomised controlled trial; RR: relative risk; SNAC: scaphoid non-union advanced collapse; UK: United Kingdom